Cap-Assisted Endoscopic Mucosal Resection of an Incidental Rectal Traumatic Neuroma - Elias Estifan; Varun Patel; Matthew Grossman (Case Reports in Gastrointestinal Medicine)
A traumatic neuroma is a well-known complication after acute trauma to a peripheral nerve; the nerve tries to re-establish continuity by an orderly growth of axons from the peripheral to distal stump through the proliferation of Schwann cells. However, this process is not always perfect, and aberrant repair gives rise to a neuroma. We present a 50-year-old female who underwent an initial colonoscopy for change in bowel habits and was found to have a 7 mm submucosal lesion in the proximal rectum. Endoscopic ultrasound was done which showed a hypoechoic lesion in the submucosal plane without muscularis propria invasion. The patient underwent successful cap-assisted endoscopic mucosal resection of the lesion without complication. Pathology of the specimen revealed a traumatic rectal neuroma with immunostaining positive for S100. However, this patient did not have any known risk factors such as previous surgery including polypectomy or hemorrhoidectomy or any previous rectal manipulation. Interestingly, this is the second case of traumatic rectal neuroma reported in the English-language literature.